A case report on gastrointestinal mucormycosis - Kumar, B. Vijay; Rao, G. Vamshi Nandan; Veena, Mettu (International Journal of Advances in Medicine, 2025)
Mucormycosis is a rare but often fatal opportunistic fungal infection and gastrointestinal (GI) mucormycosis is an uncommon subtype associated with high mortality, particularly in immunocompromised individuals such as those with diabetes, malignancy or organ failure. A 57-year-old man reported with symptoms of fever, jaundice, altered mentation and generalised weakness. He was intubated and managed in ICU for sepsis, MODS and encephalopathy. Investigations revealed hyperglycaemia, renal dysfunction and leucocytosis and were managed with several intravenous antibiotics and other supportive care, sustained low-efficiency dialysis (SLED) was performed due to hyperkalemia and metabolic acidosis, along with acute kidney injury (AKI). After an endoscopy showed an ulcerated tumor in the stomach fundus, a sleeve gastrectomy and laparotomy were carried out. Histopathology confirmed gastric mucormycosis with angioinvasion. Initial treatment with liposomal Amphotericin B (300 mg, IV, once daily) was given and stopped due to acute kidney injury and replaced by Isavuconazole (200 mg, oral, once daily). Multidisciplinary care led to clinical improvement and the patient was discharged in stable condition. Prompt endoscopic evaluation, surgical intervention, and timely antifungal therapy, especially Isavuconazole when Amphotericin B is contraindicated, can significantly enhance survival and multidisciplinary approach is vital in managing such complex infections.